Lymphatic endothelial cell immunohistochemical markers for evaluation of the intestinal lymphatic vasculature in dogs with chronic inflammatory enteropathy. (6th June 2019) - Wennogle, Sara A.; Priestnall, Simon L.; Suárez‐Bonnet, Alejandro; Soontararak, Sirikul; Webb, Craig B.
Abstract: Background: Lymphatic endothelial cell (LEC) immunohistochemical markers have identified intestinal lymphatic vasculature abnormalities in humans with inflammatory bowel disease, but have not been used to evaluate intestinal lymphatic vasculature in a group of dogs with chronic inflammatory enteropathy (CIE). Objectives: To utilize LEC markers to identify and measure intestinal lymphatic vasculature in endoscopic biopsy samples of CIE dogs. To evaluate whether measured lymphatic vasculature variables correlate with serum albumin concentrations. Animals: Twenty‐four dogs with CIE; n = 13, serum albumin concentration <2.5 g/dL (CIE‐protein‐losing enteropathy [PLE]), n = 11, serum albumin concentration ≥2.5 g/dL (CIE‐N). Methods: Prospective study. Lymphatic endothelial cell immunolabeling with Prox‐1 and LYVE‐1 performed on endoscopic biopsy samples from 24 dogs with CIE. Duodenal and ileal villous lacteal width (VLW) and proprial mucosal lacteal width (MLW) were determined for each case and analyzed for correlation with serum albumin concentration. Lacteal dilatation scores using routine H&E histopathology were assessed for correlation with immunohistochemistry (IHC)‐calculated VLW and MLW. Results: Lower serum albumin concentrations were correlated with increased VLW (rho = −.4644; P = .02) and MLW (rho = −.6514; P < .001) in the ileum. Lymphatic endothelial cell IHC identified presumptive proprial mucosal lymphangiectasia in some dogs that was not recognized with routine H&E staining. Lacteal dilatation scores were correlated with VLW in duodenum (rho = .4634; P = .02) and ileum (rho = .5292; P = .008), but did not correlate with MLW. Conclusions and Clinical Importance: Lymphatic endothelial cell immunolabeling identified presumptive proprial mucosal lymphangiectasia in CIE dogs, particularly in the ileum of hypoalbuminemic dogs. Routine evaluation of villous lacteals likely underestimates abnormalities of the lymphatic vasculature in dogs with CIE.